The Using Blooket Web as a Teaching Medium on Students’ Motivation to Learn English as a Second Language - Erlangga, Prayoga Eka Krisna (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The integration of game-based platforms like Blooket in English as a Second Language (ESL) education has gained attention for its ability to enhance student motivation and engagement. This study examines the impact of using Blooket as a teaching medium to motivate middle school students learning ESL. Blooket offers interactive, quiz-based games tailored to various learning needs, aligning with gamification principles that foster a fun and engaging environment. The research employs a mixed-method approach, combining pre- and post-test surveys and interviews, to evaluate the motivational effects of Blooket compared to traditional teaching methods. Results indicate a significant increase in motivation and engagement among students using Blooket, highlighting its potential as a tool for modern ESL education.